Method for preparing high-corrosion-resistance magnesium-rare earth alloy

By introducing rare earth elements into magnesium alloys and carrying out specific heat treatment processes, a high corrosion-resistant magnesium rare earth alloy is formed, which solves the problem of poor corrosion resistance of magnesium alloys and achieves effective protection in a corrosive environment.

CN119824261APending Publication Date: 2025-04-15CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042748.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The corrosion resistance of magnesium alloys is poor, and the corrosion products grow in the longitudinal direction, forming a loose and porous structure, which cannot form an effective protective barrier, but instead accelerates corrosion.

Method used

Mg-RE, an intermediate alloy of metal magnesium and magnesium and rare earth elements, was melted under an inert environment, and casting Mg-RE ingots were obtained, extruded and annealed, to form a highly corrosion-resistant magnesium rare earth alloy.

Benefits of technology

When the generated magnesium rare earth alloy encounters corrosion liquid, the magnesium hydroxide corrosion product grows laterally, forming a tight layered sheet-like structure, preventing the penetration of aggressive ions and significantly improving the corrosion resistance of magnesium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824261A_ABST
    Figure CN119824261A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-corrosion-resistance magnesium-rare earth alloy, and relates to the technical field of magnesium alloy materials.The method includes the steps that magnesium metal and intermediate alloy Mg-RE are smelted, a cast ingot obtained through smelting and casting is extruded and then subjected to annealing heat treatment, and the obtained magnesium-rare earth alloy forms a specific structure; when the magnesium-rare earth alloy is corroded by corrosive liquids such as NaCl solution, simulated body fluid, automobile refrigerating fluid and sulfate, a corrosion product magnesium hydroxide generated by reaction of the magnesium-rare earth alloy and the corrosive liquids transversely grows and is arranged on the surface of the magnesium-rare earth alloy in a lamellar form, and the lamellar magnesium hydroxide is tightly arranged, so that a flat, compact and stable corrosion product film layer is formed. When the magnesium-rare earth alloy prepared by the preparation method is corroded, transversely generated flaky magnesium hydroxide can effectively avoid loose and porous morphology, so that permeation and destructive effects of aggressive ions are effectively blocked, and controllable protection performance is provided for a magnesium alloy matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy materials, and in particular to a method for preparing a high corrosion-resistant magnesium rare earth alloy. Background Art

[0002] Magnesium alloys have low density, high specific strength, excellent thermal conductivity and good machinability, and therefore show wide application potential in aerospace, automobile, electronics and other fields. However, due to the active chemical properties of magnesium, its corrosion resistance is poor, which greatly limits its service life and wide application under more demanding application conditions. Studies have shown that the corrosion products of magnesium alloys tend to grow in the longitudinal direction, showing a loose and porous structure. This growth pattern and structural morphology of corrosion products not only fail to form an effective protective barrier, but also provide a channel for the invasion of aggressive ions, further accelerating the corrosion process. Therefore, how to regulate the growth direction of magnesium alloy corrosion products and promote them to form a dense and uniform protective layer has become one of the key issues in improving the corrosion resistance of magnesium alloys. Therefore, it is necessary to regulate the growth direction of corrosion products, close the invasion channel of foreign ions, prevent the penetration and destructive effect of aggressive ions, and promote the formation of corrosion products in a uniform and dense form, thereby significantly improving the corrosion resistance of magnesium alloys. This technical direction is of great significance for extending the service life of magnesium alloys and expanding their application range. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a highly corrosion-resistant magnesium rare earth alloy.

[0004] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0005] A method for preparing a highly corrosion-resistant magnesium rare earth alloy is provided, and the specific steps are as follows:

[0006] S1: melting metal magnesium and master alloy Mg-RE of magnesium and rare earth elements in an inert environment;

[0007] S2: Casting and cooling the alloy melt to obtain a Mg-RE ingot;

[0008] S3: Extruding the Mg-RE ingot to obtain a Mg-RE alloy plate;

[0009] S4: Annealing heat treatment is performed on the Mg-RE alloy sheet to obtain a highly corrosion-resistant magnesium rare earth alloy.

[0010] Furthermore, the mass ratio of the rare earth element to the high corrosion-resistant magnesium rare earth alloy is 1.0-2.0wt%.

[0011] Furthermore, the smelting in step S1 is a two-stage smelting, specifically: after keeping the temperature at 600-680°C for 20-40 minutes, the temperature is raised to 720-760°C and kept for 25-35 minutes to obtain a Mg-RE alloy melt.

[0012] Furthermore, during the process of heating to 720° C. to 760° C., the molten alloy is stirred, and after heating to the rated temperature, it is kept at a temperature for 25 to 35 minutes.

[0013] Furthermore, between steps S2 and S3, the Mg-RE alloy melt needs to be solution treated at a temperature of 320 to 580° C. for a time of 12 to 48 hours.

[0014] Furthermore, in step S3, the extrusion rate of the Mg-RE ingot is 2-12 mm / min, and the extrusion ratio is 8-52.

[0015] Furthermore, when the Mg-RE ingot is extruded, it is carried out at an environment of 220 to 380°C.

[0016] Furthermore, the annealing heat treatment is specifically: keeping the temperature at 250-350° C. for 1 h to 12 h.

[0017] The beneficial effects of the present invention are:

[0018] The present invention melts metal magnesium and an intermediate alloy Mg-RE, extrude the ingot obtained by melting and casting, and then performs annealing heat treatment, so that the obtained magnesium rare earth alloy forms a unique structure. When encountering corrosion liquids such as NaCl solution, simulated body fluid, automobile refrigerant, sulfate, etc., the corrosion product magnesium hydroxide generated by the reaction of the magnesium rare earth alloy with the corrosion liquid grows laterally and is arranged in a lamellar form on the surface of the magnesium rare earth alloy, and the lamellar magnesium hydroxide is arranged closely, thereby forming a flat, dense and stable corrosion product film layer.

[0019] When the magnesium alloy prepared by the prior art encounters corrosion, the magnesium hydroxide on the surface grows longitudinally on the surface of the magnesium alloy, and there are large pores between the lamellae, which provides a channel for the entry of aggressive ions and accelerates the corrosion of the magnesium alloy. When the magnesium rare earth alloy prepared by the preparation method of the present invention encounters corrosion, the flaky magnesium hydroxide generated laterally can effectively avoid the loose and porous morphology, thereby effectively blocking the penetration and destructive effects of aggressive ions, and providing controllable protection performance for the magnesium alloy matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the magnesium-scandium alloy after corrosion obtained in Example 1;

[0021] Figure 2 This is a scanning electron microscope image of the magnesium-scandium alloy after corrosion obtained in Example 3;

[0022] Figure 3 This is a scanning electron microscope image of the magnesium-scandium alloy after corrosion obtained in Example 5;

[0023] Figure 4 This is a scanning electron microscope image of the magnesium-scandium alloy after corrosion obtained in Example 6;

[0024] Figure 5 This is a scanning electron microscope image of the magnesium-scandium alloy obtained in Example 8 after corrosion. DETAILED DESCRIPTION

[0025] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0026] Example 1

[0027] A method for preparing a highly corrosion-resistant magnesium rare earth alloy. The present invention takes the rare earth element scandium Sc as an example and adopts the following method to prepare the magnesium scandium alloy:

[0028] S1: Weighing magnesium metal and magnesium and master alloy Mg-Sc into a vacuum melting furnace, and melting in an inert environment; the inert environment is created by a mixed gas of SF6 and CO2, and the volume ratio of SF6 and CO2 is 1: (350-450); when weighing the master alloy Mg-Sc, ensure that the mass ratio of Sc to the magnesium-scandium alloy is 1.5wt%. In other embodiments of the present invention, the mass ratio of the rare earth element to the magnesium-rare earth alloy can be within 1.0-2.0wt%, and preferably not more than 2.0wt%.

[0029] The smelting is a two-stage smelting, specifically: after keeping the temperature at 600-680°C for 20-40 minutes, the temperature is raised to 720-760°C. During the heating process to 720-760°C, a magnetic stirrer is used to stir the molten alloy. After the temperature is raised to the rated temperature, the alloy is kept at the temperature for 25-35 minutes to obtain a Mg-Sc alloy melt.

[0030] S2: Casting and cooling the alloy melt to obtain a Mg-Sc ingot; in the specific implementation, the casting mold is preheated before casting, and the casting mold is preheated to 280° C. to 420° C. before pouring the alloy melt into it.

[0031] The Mg-Sc ingot is subjected to a solution treatment at a temperature of 320 to 580° C. and a time of 12 to 48 hours.

[0032] S3: The Mg-Sc ingot is extruded to obtain a Mg-Sc alloy sheet; the extrusion is carried out at 320° C., the extrusion rate is 2 mm / min, and the extrusion ratio is 30.

[0033] In specific implementation, the extrusion environment temperature is 320-580°C, the extrusion rate is 2-12mm / min, and the extrusion ratio is 8-52; combined with solid solution treatment and subsequent annealing heat treatment, the corrosion resistance of the magnesium-scandium alloy can be improved, the difference lies in the amount of improvement.

[0034] S4: annealing the Mg-Sc alloy plate to obtain a high corrosion-resistant magnesium-sc alloy. The annealing heat treatment is specifically: keeping the temperature at 300° C. for 8 hours.

[0035] In specific implementation, the temperature of the annealing heat treatment can be in the range of 250-350° C., preferably not more than 350° C., or lower than 250° C. The holding time of the annealing heat treatment can be in the range of 1 h to 12 h, preferably not more than 12 h.

[0036] Example 2

[0037] The difference between this embodiment and embodiment 1 is that the mass ratio of Sc to the mass ratio of the magnesium rare earth alloy is 0.5wt%, and in this embodiment, the Mg-RE alloy plate is not subjected to heat treatment, and the Mg-RE alloy plate is used as a magnesium-scandium alloy.

[0038] Example 3

[0039] The difference between this embodiment and embodiment 2 is that the mass ratio of Sc to the mass ratio of the magnesium rare earth alloy is 1.5wt%.

[0040] Example 4

[0041] The difference between this embodiment and embodiment 2 is that the mass ratio of Sc to the mass ratio of the magnesium rare earth alloy is 3.0wt%.

[0042] Example 5

[0043] The difference between this embodiment and embodiment 1 is that the holding time of the annealing heat treatment is 2 hours.

[0044] Example 6

[0045] The difference between this embodiment and embodiment 1 is that the holding time of the annealing heat treatment is 15 hours.

[0046] Example 7

[0047] The difference between this embodiment and embodiment 4 is that the temperature of the annealing heat treatment is 400°C.

[0048] Example 8

[0049] The difference between this embodiment and embodiment 1 is that the Mg-Sc ingot is not extruded but directly heat treated.

[0050] Example 9

[0051] The magnesium-scandium alloys prepared in Examples 1-8 were taken. The preparation parameters of the magnesium-scandium alloys in Examples 1-8 are shown in Table 1.

[0052] Table 1

[0053] Sc / wt.% Whether to squeeze Heat treatment temperature / ℃ Heat treatment time / h Example 1 1.5 yes 300 8 Example 2 0.5 yes / / Example 3 1.5 yes / / Example 4 3.0 yes / / Example 5 1.5 yes 300 2 Example 6 1.5 yes 300 15 Example 7 1.5 yes 400 2 Example 8 1.5 no 300 8

[0054] The prepared magnesium-scandium alloy was subjected to hydrogen evolution experiment and weight loss experiment in 3.5wt% NaCl solution. The experimental results are shown in Table 2.

[0055] Table 2

[0056]

[0057] It can be seen from Table 2 that Example 1 has the lowest hydrogen evolution rate and weight loss rate, that is, the magnesium-scandium alloy prepared in Example 1 has the best corrosion resistance.

[0058] Compared with Example 1, Example 3 did not undergo annealing heat treatment. Obviously, the hydrogen evolution rate and weight loss rate of Example 3 were greater than those of Example 1. The surface of Example 1 after being corroded by 3.5wt% NaCl solution was photographed using a scanning electron microscope, and the following was obtained: Figure 1 As shown, the surface of Example 3 after being corroded by 3.5wt% NaCl solution was photographed, and the following Figure 2 shown by Figure 1 and Figure 2 It can be seen that the corrosion product of the magnesium-scandium alloy without annealing heat treatment is a lamellar structure growing vertically, with large pores, providing a path for the penetration of aggressive ions. The corrosion product of the magnesium-scandium alloy of Example 1 that has been annealed heat treated shows a triangular lamellar structure growing horizontally, with layers interlaced and tightly connected, with almost no obvious pores, which can effectively block the invasion of aggressive ions and significantly improve the corrosion resistance of the magnesium-scandium alloy.

[0059] Comparing Examples 2-4, it can be seen that with the increase of Sc content, the hydrogen evolution rate and weight loss rate of the alloy both show a trend of first decreasing and then increasing, which indicates that with the increase of Sc content, the corrosion resistance of the alloy first increases and then decreases. This is mainly related to the effect of Sc on the microstructure of magnesium alloy. When the Sc content is 3.0wt%, the hydrogen evolution rate exceeds 0.07mL·cm -2 ·h -1 , the weight loss rate exceeds 2 mg·cm -2 ·d -1 .

[0060] By comparing Examples 1, 5, and 6, it can be seen that as the annealing heat treatment time increases, the hydrogen evolution rate and the weight loss rate first decrease and then increase. Too long annealing heat treatment time is not conducive to the regulation of the growth direction of the corrosion products, causing the magnesium hydroxide to transform into longitudinal growth, resulting in the appearance of pores.

[0061] However, the hydrogen evolution rate and weight loss rate of Examples 1, 5, and 6 are lower than those of Examples 2-4 which are not subjected to annealing heat treatment. Annealing heat treatment may affect the corrosion resistance of the magnesium rare earth alloy.

[0062] The surfaces of Example 5 and Example 6 after being corroded by 3.5wt% NaCl solution were photographed using a scanning electron microscope, and the following results were obtained: Figure 3 and Figure 4 ;Depend on Figure 4 It can be seen that when the heat treatment time is short, some transverse flakes have been generated on the surface of the corroded magnesium-scandium alloy, and the hydrogen evolution rate and weight loss rate can be seen, which shows that it has better corrosion resistance.

[0063] The hydrogen evolution rate and weight loss rate of Example 7 are significantly higher than those of Examples 1-6. This is because when the heat treatment temperature is too high, the grain size of the alloy is significantly coarsened, which is not conducive to the continuity of the corrosion products, and local corrosion is prone to occur, accelerating the corrosion of the alloy. When the heat treatment temperature is too high, the growth direction of the corrosion products is difficult to control and will still grow along the longitudinal direction, which is not conducive to the formation of a dense corrosion product film and cannot provide effective protection for the substrate.

[0064] The hydrogen evolution rate and weight loss rate of Example 8 are significantly higher than those of Example 1. The surface of Example 8 after being corroded by 3.5wt% NaCl solution was photographed using a scanning electron microscope. The results are as follows: Figure 5 As shown by Figure 5 It can be seen that the corrosion products on the surface of Example 8 did not form flakes, and the extrusion process was able to improve the microstructure of the alloy, making it more conducive to regulating the growth of corrosion products.

[0065] During the preparation of magnesium-scandium alloy, the extrusion process and annealing heat treatment can greatly improve the corrosion resistance of magnesium-scandium alloy. When the annealing heat treatment is performed, the corrosion resistance is best when the annealing temperature is 300℃ and the insulation time is 8h.

[0066] In summary, the method proposed in the present invention can be used to prepare a magnesium-scandium alloy with high corrosion resistance, and the rare earth elements have similar properties. In the preparation of other magnesium-rare earth alloys, that is, in other embodiments of the present invention, the rare earth element scandium Sc can also be replaced by lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium or yttrium.

Claims

1. A method for preparing a highly corrosion-resistant magnesium rare earth alloy, characterized in that: The specific steps are as follows: S1: melting metal magnesium and master alloy Mg-RE of magnesium and rare earth elements in an inert environment; S2: Casting and cooling the alloy melt to obtain a Mg-RE ingot; S3: Extruding the Mg-RE ingot to obtain a Mg-RE alloy plate; S4: Annealing heat treatment is performed on the Mg-RE alloy sheet to obtain a highly corrosion-resistant magnesium rare earth alloy.

2. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 1, characterized in that: The mass ratio of the rare earth element to the high corrosion resistant magnesium rare earth alloy is 1.0-2.0wt%.

3. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 1, characterized in that: The smelting in step S1 is a two-stage smelting, specifically: after keeping the temperature at 600-680° C. for 20-40 minutes, the temperature is raised to 720-760° C. and kept for 25-35 minutes to obtain a Mg-RE alloy melt.

4. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 3, characterized in that: During the process of heating to 720-760°C, the molten alloy is stirred, and after heating to the rated temperature, it is left to stand and keep warm for 25-35 minutes.

5. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 1, characterized in that: Between the steps S2 and S3, the Mg-RE alloy melt needs to be subjected to a solution treatment, the temperature of the solution treatment is 320 to 580° C., and the time of the solution treatment is 12 to 48 hours.

6. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 1, characterized in that: In step S3, the extrusion rate of the Mg-RE ingot is 2-12 mm / min, and the extrusion ratio is 8-52.

7. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 6, characterized in that: When the Mg-RE ingot is extruded, it is carried out at 220 to 380°C.

8. The method for preparing a highly corrosion-resistant magnesium rare earth alloy according to claim 1, characterized in that: The annealing heat treatment is specifically: keeping the temperature at 250-350° C. for 1 h to 12 h.

9. A highly corrosion-resistant magnesium rare earth alloy prepared by the method according to any one of claims 1 to 8.